Assessment of mammal reproduction for hunting sustainability through community‐based sampling of species in the wild. Issue 4 (7th March 2017) - Mayor, Pedro; El Bizri, Hani; Bodmer, Richard E.; Bowler, Mark
Abstract: Wildlife subsistence hunting is a major source of protein for tropical rural populations and a prominent conservation issue. The intrinsic rate of natural increase. ( rmax ) of populations is a key reproductive parameter in the most used assessments of hunting sustainability. However, researchers face severe difficulties in obtaining reproductive data in the wild, so these assessments often rely on classic reproductive rates calculated mostly from studies of captive animals conducted 30 years ago. The result is a flaw in almost 50% of studies, which hampers management decision making. We conducted a 15‐year study in the Amazon in which we used reproductive data from the genitalia of 950 hunted female mammals. Genitalia were collected by local hunters. We examined tissue from these samples to estimate birthrates for wild populations of the 10 most hunted mammals. We compared our estimates with classic measures and considered the utility of the use of rmax in sustainability assessments. For woolly monkey ( Lagothrix poeppigii ) and tapir ( Tapirus terrestris ), wild birthrates were similar to those from captive populations, whereas birthrates for other ungulates and lowland‐paca ( Cuniculus paca ) were significantly lower than previous estimates. Conversely, for capuchin monkeys ( Sapajus macrocephalus ), agoutis ( Dasyprocta sp .), and coatis ( Nasua nasua ), our calculated reproductive rates greatly exceeded often‐used values. Researchers could keep applying classic measures compatible with our estimates, but for other species previous estimates of rmax may not be appropriate. We suggest that data from local studies be used to set hunting quotas. Our maximum rates of population growth in the wild correlated with body weight, which suggests that our method is consistent and reliable. Integration of this method into community‐based wildlife management and the training of local hunters to record pregnancies in hunted animals could efficiently generate useful information of life histories of wild species and thus improve management of natural resources.